As contribuições do Ministério Público ao enfrentamento ao tráfico de pessoas no estado da Paraíba à luz das políticas públicas - Lima, Mariane Izabel Silva dos Santos (2021)
Human trafficking is a highly complex crime whose confrontation involves a series of challenges and agents, including the Brazilian Public Prosecution Office, whose performance is analyzed in this dissertation. Therefore, the study initially discusses the meaning of human trafficking, given that this crime is characterized by a series of conceptual problems. Then, the research seeks to understand, based on public policies, how the fight against human trafficking in Brazil should work. For that intent, the study analyzed — not only from the perspective of criminal repression but also of prevention and protection — the structure that is present in international documents and in the National Policy Against Human Trafficking. Subsequently, the study discusses which agents and institutions are involved in this fight, among which the attributions, responsibilities and capacities of the Public Prosecution Office were emphasized in this context, especially in the state of Paraíba, between the years 2016 to 2019. This exploratory study is being methodologically instrumentalized from the dialectical method, as it enables a better appropriation of reality when considering the complexity of situations, which is a fundamental premise for dealing with human trafficking. In addition, the study has qualitative and descriptive approaches and an empirical stage — the field research — through structured interview, with open questions, to prosecutors of the Public Prosecution Office of the State of Paraíba (MPPB), prosecutors of the Federal Public Prosecution Office (MPF) as well as of the Public Prosecution Office for Labor (MPT). Data analysis was performed through the content analysis proposed by Bardin (2011), which allowed the creation and appreciation of five categories especially focused on crime prevention and the protection of victims of human trafficking. The overall results show that the three branches of the Public Prosecution Office have sought to develop works that prevent crime and protect the victim, in different proportions, nonetheless. The MPPB initiated activities focused on the subject only in 2018, which totals few, but continuous actions to address this crime. Furthermore, it has sought to train civil servants and members of the office to deal with this issue. The MPT works diligently with several tools to prevent this crime, such as the use of busdoors, social media sharing and investment, with resources for judicial convictions of companies that violated labor rights, in projects aimed at training children, adolescents and young people, aiming to reduce the social vulnerability in which they are inserted. In addition, the MPT seeks to act in an intersectorial way to confront crime and it has a strong critical sense of the improvements to be made regarding this crime. Finally, the MPF was the branch that presented clarification activities, closer to the population, with interviews on popular channels. However, few projects were carried out by the MPF at a local level in the state of Paraíba. The study concludes that, despite the existence of important projects, actions and works being developed in the state of Paraíba, greater interest as well as personal and financial investment are still needed so that the fight against this crime can evolve.